The Past and Present: A Correlation Analysis between Environmental Factors of the Neolithic and Chalcolithic Sites in the Bakhtiari Highlands with an Ethnoarchaeological Approach - Mohsen Heydari Dastenaei; Ali Asghar Nowrouzi; Mehdi Mortazavi (Iranian Journal of Archaeological Studies, 2021)
Laran district, located at the southern basin of the Zayandeh Roud River, has been an eligible location for human settlements throughout historic/prehistoric periods due to its geographical conditions and significant environmental potential. This part of the Zagros Mountains is one of the foremost regions between the Central Plateau and Khuzestan Province thus with its environment plays a crucial role in forming, maintaining, or destroying archaeological sites. This research is descriptive-analytical that studies 27 Neolithic and Chalcolithic sites identified through the archaeological survey analysis accomplish in the Laran district in 2010. Arc GIS was used to facilitate the understanding of spatial patterns through environmental factors. This software combines the existing distances and the data related to environmental conditions with the locations of the sites then offers the results in the form of numbers. Pearson’s Correlation analysis was used to examine the relations between archaeological sites and environmental factors. Existing or lack of correlation among archaeological sites depends on the human’s relationship with their environment which generates a particular kind of perspective. In the present study, the extent of archaeological sites serves as the dependent variable and environmental conditions such as distance from water resources and access routes, the vegetation, the aspect and the degree of slopes, and above sea level (elevation) are independent variables. Additionally, archaeological studies using the same analytical method were accomplished in 61 campsites in the district and the results resembled Neolithic and chalcolithic sites of the Laran district. The results show that settlements in the Laran district are rarely dependent upon environmental factors, which means that the mentioned settlements, similar to present campsites, were used on a seasonal, temporary basis.